Farmers’ criteria for maize (Zea mays L.) selection in Villaflores and Villa Corzo, Chiapas, Mexico - Delgado-Ruiz, Fredy (Universidad Autónoma de Tamaulipas, 2018)
The maize production in Chiapas implies the decision to grow local or hybrid maize. The latter present higher yields characteristics, but demand more inputs, particularly those related to soil degradation, water pollution, genetic diversity and knowledge losses over local maize varieties. The objective of this research was to identify the criteria used by small maize farmers in the election of seed for sowing in the Villaflores and Villa Corzo municipalities (Chiapas). The data were gathered through semi-structured interviews with farmers’ participating in the ASERCA program and analyzed by percentages and frequencies. The hybrid maize is the most preferred variety by the small farmers in both municipalities, although some still prefer local maize (native) or bet on the cultivation of both due to use and customs reasons. The selectionof hybrid maizeseeds in both municipalities is based mainly on better yield characteristics, although in Villa Corzo, the selection of local varieties is due to their better resistance against pests and diseases. Additional criteria used to select the local seeds were: better lodging resistance, better moisture resistance, lower plant height, less seed rot and better drought tolerance. In local maize varieties, seed yield was considered an important factor in both municipalities, but a greater resistance against pests and diseases was only considered in Villa Corzo. The highest sale price was not an important consideration in neither of the two municipalities. Other criteria used to select the local seeds were better drought tolerance, seed lower cost, greater ear size, personal interest in conserving the local resource, better flavor and the possibility for the rotation of local varieties. The six wished characteristics of local maize varieties to be improved were: a lower plant height, a better yield, a better resistance to humidity and lodging, a greater grain weight, and a bigger size  of  ears  and  grains.